Адаптивные особенности и филогения огнецветок (Coleoptera, Pyrochroidae) в свете изучения личиночных форм - Потоцкая, В.А. (Вестник зоологии, 1984)
﻿Two ecological factors suggested to play the major role in larval morphogenesis of the Pyrochroidae: movement within narrow, fissure-like space under the bark, and feeding on hard phloem. Accordingly, the main trend of morphological adaptations leads to the appearance of characters, improving locomotory system and those giving additional support to the mouthparts and head capsule consolidation. Of five genera under study, Pseudopyrochroa is suggested to be the most archaic with following progressive succession: Pyrochroa - Dendroites - Schizotus - Pogonocerus.